The Philosophy of Software - Berry, D. author. aut Link
XI, 200 p.
Keywords: This book is a critical introduction to code and software that develops an understanding of its social and philosophical implications in the digital age. Written specifically for people interested in the subject from a non-technical background, the book provides a lively and interesting analysis of these new media forms.